Staffing and the incidence of pressure ulcers in German hospitals: A multicenter cross‐sectional study. (3rd July 2016) - Schneider, Paul Peter; Geraedts, Max
Abstract: In this study, we investigated the association between nurse and physician staffing and the incidence of hospital‐acquired pressure ulcers in acute care hospitals in Germany. The study population, derived from the Quality Reports of German Hospitals and the Hospital Directory, consisted of 710 hospitals covering 716, 281 cases in the first quarter of 2010, and 672 hospitals covering 757, 665 cases in the first quarter of 2012. The relationship between staffing variables and the standardized incidence ratios of pressure ulcers was examined using bivariate and multivariable linear regression models. Estimates were controlled for several patient and hospital characteristics. The total number of nurses and physicians per 100 beds did not show significant associations with outcome variables. However, the proportion of nurses with at least 3 years of training to total nursing staff was inversely associated with the incidence of pressure ulcers at hospital level, indicating a higher efficacy of pressure ulcer‐prevention measures.